TERRANES OF THE EASTERN ARCTIC SHELF OF RUSSIA - Kos'ko M.K. (My University, 2007)
We propose the first tectonic subdivision of the basement of the East Antarctic shelf of Russia based on recent investigations of the block structure of the Eurasian continental margin of the Arctic Ocean and extrapolation with continental and insular land. The proposed scheme of subdivision (figure) is based on principles of terrane analysis developed by Russian and foreign scientists.